2018
DOI: 10.1089/jamp.2017.1418
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes: Exposure and Use Among Pediatric Populations

Abstract: As an emerging inhalational exposure, electronic cigarettes (e-cigarettes) have rapidly gained public awareness with increasing use among adolescents and adults, leading to increased primary use by adolescents and increased secondhand exposure to emissions in infants, children, and adolescents. Although the long-term health risks for primary use and secondhand emission exposure are unknown, limited data from animal studies suggest that there is the potential for long-term lung injury and altered neurocognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…There are now several hundreds of ENDS products on the market, with a recent study noting that ~ 430 different brands were available in 2017 4 , and this category of tobacco product is projected to become a $61.4 billion business by 2025 5 . Concomitantly, the demographic of ENDS users has shifted towards teens and young adults 6 . There is a growing concern of nicotine addiction among youth and for the use of ENDS to serve as a potential gateway for other tobacco products such as cigarettes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There are now several hundreds of ENDS products on the market, with a recent study noting that ~ 430 different brands were available in 2017 4 , and this category of tobacco product is projected to become a $61.4 billion business by 2025 5 . Concomitantly, the demographic of ENDS users has shifted towards teens and young adults 6 . There is a growing concern of nicotine addiction among youth and for the use of ENDS to serve as a potential gateway for other tobacco products such as cigarettes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent US Centers for Disease Control and Prevention (CDC) report indicated that aerosols from e-cigarettes may also contain lead, carcinogens, and volatile organic compounds 18 . These compounds can potentially damage lung and neurocognitive development in humans, which is already proven in animal studies 19 . Using e-cigarettes has also been known to worsen asthma symptoms, which is concerning, in particular for youth, due to a recent study showing that 22.5% of asthmatic adults aged ≥18 years reported currently using e-cigarettes 20 .…”
Section: Introductionmentioning
confidence: 91%
“…As regards e-cigarettes potential harmful effects, consideration should be given to acute injuries. A fair amount of reports to poison centers concern children incidentally exposed to e-cig liquids through ingestion (70%), inhalation (15%), ocular (8.5%) and dermal contact (6%) 140 . Nicotine poisoning can result in tachycardia, dizziness and even seizures 141 .…”
Section: Acute Adverse Effectsmentioning
confidence: 99%